Pengaruh Knowledge Sharing dan Kompetensi Terhadap Organizational Citizenship Behavior Dimoderasi Motivasi Studi Kasus pada Desa Wisata Nusantara (DEWISNU) Provinsi Jawa Tengah - Eva Agustina Megasari; Tristiana Rijanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the effect of Knowledge Sharing and Competence on Organizational Citizenship Behavior (OCB) with Motivation as a moderating variable on the administrators of Desa Wisata Nusantara (Dewisnu) in Central Java Province. This study was conducted to understand how knowledge sharing and individual competence contribute to positive organizational behavior, and to what extent study motivation strengthens the relationship. This study involved 107 administrators of Desa Wisata Nusantara as the research population. Data were obtained through questionnaires and analyzed using IBM SPSS. The method used was Non-Probability Sampling with Saturated Sampling Technique, where all members of the population were used as research samples. The results showed that Knowledge Sharing had a positive impact on Organizational Citizenship Behavior. Likewise, Competence had a positive effect on Organizational Citizenship Behavior. In addition, Motivation strengthened the relationship between Knowledge Sharing and OCB, and increased the effect of Competence on OCB.